Role of Tonsillar Chronic Inflammation and Commensal Bacteria in the Pathogenesis of Pediatric OSA - Sarmiento Varón, Lindybeth; De Rosa, Javier; Rodriguez, Raquel; Fernández, Pablo M.; Billordo, L. Ariel; Baz, Plácida; Beccaglia, Gladys; Spada, Nicolás; Mendoza, F. Tatiana; Barberis, Claudia M.; Vay, Carlos; Arabolaza, M. Elena; et al. (Frontiers in Immunology, 2021)
Immune responses at the boundary between the host and the world beyond are complex and mucosal tissue homeostasis relies on them. Obstructive sleep apnoea (OSA) is a syndrome suffered by children with hypertrophied tonsils. We have previously demonstrated that these tonsils present a defective regulatory B cell (Breg) compartment. Here, we extend those findings by uncovering the crucial role of resident pro-inflammatory B and T cells in sustaining tonsillar hypertrophy and hyperplasia by producing TNFa and IL17, respectively, in ex vivo cultures. Additionally, we detected prominent levels of expression of CD1d by tonsillar stratified as well as reticular epithelium, which have not previously been reported. Furthermore, we evidenced the hypertrophy of germinal centers (GC) and the general hyperplasia of B lymphocytes within the tissue and the lumen of the crypts. Of note, such B cells resulted mainly (IgG/IgM)+ cells, with some IgA+ cells located marginally in the follicles. Finally, by combining bacterial culture from the tonsillar core and subsequent identification of the respective isolates, we determined the most prevalent species within the cohort of OSA patients. Although the isolated species are considered normal oropharyngeal commensals in children, we confirmed their capacity to breach the epithelial barrier. Our work sheds light on the pathological mechanism underlying OSA, highlighting the relevance taken by the host immune system when defining infection versus colonization, and opening alternatives of treatment.